Tax arrears and tax litigiousness in Peru, some aspects to be considered - Sevillano, Sandra (2014)
Tax arrears are a frequent feature in many States and a concern that demands to reflect on the diverse variables that promote, cause or block their reduction. This paper elaborates on some of the variables that could promote or contribute to generate tax arrears and on some aspects of the Peruvian tax system that could help to explain the current level of tax arrears and the tax litigiousness in Peru. Tax Administration pitfalls that contribute to the generation of tax arrears and tax litigiousness are not avoided but are certainly not the core part of this work.